CAUSES ET EFFETS DES CONFLITS FONCIERS A BOKALA DANS LE TERRITOIRE DE YAHUMA ( RDC/Kin) - alaly Likunde, Simon- Pierre; Mbole, Laurent Alemo; BONGENDE, Léa MBASA (IJRDO - Journal of Social Science and Humanities Research, 2017)
For years the inhabitants of Bokala are in conflict with the inhabitants of Yanongo group. This study allows determine the causes and the effects of this conflict. We are resorting to inquiry method and interview technic. The research population is every inhabitant of the Bokala group. 50 persons were involved in the survey for only village. We examined the genesis of this conflict, the nature, several causes which are: The economic causes: the land(basic) value and the unemployment of the population; the demographic cause: the increase of the population; The ecological cause: the decrease of the ground space; The physical causes: the well-defined limit, the incapacity to cultivate the virgin forest; the psychological causes: the hatred, the antipathy, the refusal to leave, the egoism, the social prestige, the sadism, the dominance; and several effects especially negatives of this conflict, in particular: the transmission of the disease "Onchocerciasis" of people of Yanongo to the people of Bokala; the employ of idols; the death of a lot of people further to this disease and to the fight; the disappearance of more than ten villages of grouping Bokala continuation(suite) in the death of people. The disappeared villages are: Boyela, Lomame, Yalikito, Piko, Efimi, Yalotombe Wamba, Bokombe; the travel (movement) of two villages of grouping Bokala: Liabo and Liombo. The negotiation is proposed to solve this conflict.